Populism and television in Peru: From the media of the masses to the masses of the media - Protzel, Javier (1986)
The almost fifty-four years that separate the harangue from Haya de la Torre in the Plaza de Acho from the meeting with which Alan García closes his campaign on the Paseo de la República - prolonged by successive presidential "balconazos" - would illustrate with ease how certain features of the Subaltern cultures endure in spite of the obvious and important differences of characterization that throughout this long period we find in Peruvian society. However, that smell of crowds is inseparable from the way in which the masses construct the real through the means of communication; the field of view of political science should be extended to the study of mass culture to grasp the permanent and the changing in a broader dimension. In this essay a theoretical reflection on the subject is outlined.